Surveying the potential of secreted antimicrobial peptides to enhance plant disease resistance - Breen, Susan; Solomon, Peter S.; Bedon, Frank; Vincent, Delphine (Frontiers in Plant Science, 2015)
Antimicrobial peptides (AMPs) are natural products found across diverse taxa as part of the innate immune system against pathogen attacks. Some AMPs are synthesised through the canonical gene expression machinery and are called ribosomal AMPs. Other AMPs are assembled by modular enzymes generating nonribosomal AMPs and harbour unusual structural diversity. Plants synthesise an array of AMPs, yet are still subject to many pathogen invasions. Crop breeding programs struggle to release new cultivars in which complete disease resistance is achieved, and usually such resistance becomes quickly overcome by the targeted pathogens which have a shorter generation time. AMPs could offer a solution by exploring not only plant-derived AMPs, related or unrelated to the crop of interest, but also non-plant AMPs produced by bacteria, fungi, oomycetes or animals. This review highlights some promising candidates within the plant kingdom and elsewhere, and offers some perspectives on how to identify and validate their bioactivities. Technological advances, particularly in mass spectrometry (MS) and nuclear magnetic resonance (NMR), have been instrumental in identifying and elucidating the structure of novel AMPs, especially nonribosomal peptides which cannot be identified through genomics approaches. The majority of non-plant AMPs showing potential for plant disease immunity are often tested using in vitro assays. The greatest challenge remains the functional validation of candidate AMPs in plants through transgenic experiments, particularly introducing nonribosomal AMPs into crops.